Exploring The Influence Of Vitamin D In The Management Of Acne Vulgaris: A Pilot Study - Aqsa Naheed; Aashi Mughal; Tehzeeb Zehra; Rahila Aamir; Samina Fida; Taha Naveed (Journal of Rawalpindi Medical College)
Objective: The study aimed to explore the potential benefits of vitamin D supplementation in improving acne severity.